Works councils and the anatomy of wages - John T. Addison; Paulino Teixeira; Thomas Zwick (Institute for the Study of Labor (IZA), 2006)
This paper provides the first full examination of the effect of German works councils on wages using matched employer-employee data (specifically, the LIAB for 2001). We find that works councils are associated with higher earnings. The wage premium is around 11 percent (and is higher under collective bargaining). This result persists after taking account of worker and establishment heterogeneity and the endogeneity of works council presence. Next, using quantile regressions, we find that the works council premium is decreasing with the position of the worker in the wage distribution. And it is also higher for women than for men. Finally, the works council wage premium is associated with longer job tenure. This suggests that some of the premium is a noncompetitive rent, even if works council voice may dominate its distributive effects insofar as tenure is concerned.
urn:nbn:de:101:1-2008051653
Keywords: 330